2019
DOI: 10.1002/ejoc.201801678
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO and Silver‐Mediated Intermolecular Phosphonylation of Alkenes: Stereoselective Synthesis of (E)‐Alkenylphosphonates

Abstract: An efficient method was developed towards the synthesis of alkenylphosphonates from simple olefins and phosphonate diesters. This method was enabled by the use of cheap and commercially available silver salts and TEMPO. This method exhibits of good functional group tolerance, specific (E)‐selectivity for all olefins and vinyl selectivity for aliphatic olefins. A radical mechanism was proposed, and TEMPO was involved in the product formation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In the presence of an alkene, the trifluoromethyl radical adds to it before being trapped by an amidoxyl radical . Similarly, P radicals generated by oxidation with silver salts can add to styrene derivatives, and trapping with TEMPO results in the corresponding alkoxyamines that readily eliminate TEMPOH to eventually provide ( E )-alkenylphosphonates …”
Section: Nitroxides In Free-radical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of an alkene, the trifluoromethyl radical adds to it before being trapped by an amidoxyl radical . Similarly, P radicals generated by oxidation with silver salts can add to styrene derivatives, and trapping with TEMPO results in the corresponding alkoxyamines that readily eliminate TEMPOH to eventually provide ( E )-alkenylphosphonates …”
Section: Nitroxides In Free-radical Chemistrymentioning
confidence: 99%
“…1269 Similarly, P radicals generated by oxidation with silver salts can add to styrene derivatives, and trapping with TEMPO results in the corresponding alkoxyamines that readily eliminate TEMPOH to eventually provide (E)-alkenylphosphonates. 1270 The group of Chemler developed copper-mediated intramolecular cyclization of sulfonamides 1271,1272 or diarylamines 1273 to alkenes through an aminocupration. It was suggested that after the aminocupration, the resulting copper-(II)−carbon bond is homolytically cleaved, and the generated alkyl radical is then trapped with TEMPO.…”
Section: Trapping Of C-centered Radicalsmentioning
confidence: 99%
“…Because of its unique properties, the synthesis of alkenyl phosphonate has been widely developed. ,, A representative method starts from functional olefins (Scheme a). Traditionally, the vinyl phosphorus compounds are prepared from the reactions of functional olefins with P–H species, for example, enaminone phosphonation by the cleavage of C­(sp 2 )–N bond, decarboxylative phosphorylation of cinnamic acids, Hirao-type coupling of P–H reagents with alkenyl halides or alkenyl triflates, desulfonative coupling of various sulfones with phosphites, phosphonation of nitroolefins through denitration process, and direct coupling of styrenes and H -phosphites …”
Section: Introductionmentioning
confidence: 99%
“…19,20 To overcome these drawbacks, the use of porous scaffolds or hydrogels as effective local delivery carriers has been reported. [21][22][23][24][25][26] PTT agents have been hybridized with polymers or ceramics to construct photothermal composite scaffolds. 27,28 Furthermore, PTT agents and anticancer drugloaded thermosensitive liposomes have been incorporated into polymer porous scaffolds to form composite scaffolds with good photothermal conversion and controllable drug release properties.…”
Section: Introductionmentioning
confidence: 99%